The problem of moral justification and feminist ethics - Pereira, Viviane Magalhães (2020)
This paper focuses on the philosophical problem of moral justification with the aim of presenting the sense and validity of a feminist ethics. It is assumed that a feminist ethics would differ from the ancient ethics and would present an adequate alternative to the problem of moral justification as well of the current moral conflicts. It proposes a solution which follows a logic built by a determined human praxis. In other words, the aim of this paper is to help understand how a content of morality resulted from historical, temporal e cultural elements can be constructed. Such elements in this case are related to the women’s conditions arising in the social environment. But that requires that a new conception of ethics be presented to guide a solution to current moral conflicts as the Carol Gilligan’s feminist ethics of care.